2021
DOI: 10.1038/s41377-021-00503-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantum engineering of non-equilibrium efficient p-doping in ultra-wide band-gap nitrides

Abstract: Ultra-wide band-gap nitrides have huge potential in micro- and optoelectronics due to their tunable wide band-gap, high breakdown field and energy density, excellent chemical and thermal stability. However, their application has been severely hindered by the low p-doping efficiency, which is ascribed to the ultrahigh acceptor activation energy originated from the low valance band maximum. Here, a valance band modulation mode is proposed and a quantum engineering doping method is conducted to achieve high-effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…Developing more materials is necessary to further improve the performance of SPE sources. 2D III-nitrides semiconductors show great potential to provide more options in this field not only due to the chemical comparability to h -BN but also due to the mature development of their bulk phases, such as deep UV light-emitting diodes, , lasers diodes, , and transistors . Following theoretically confirming the good thermodynamic stability of hexagonal AlN ( h -AlN), Tsipas et al, Mansurov et al, and Malin et al had experimentally realized h -AlN via molecular beam epitaxy. The defective monolayer h -AlN is highly expected to be a good host material for qubits due to its similarity to h -BN.…”
Section: Introductionmentioning
confidence: 99%
“…Developing more materials is necessary to further improve the performance of SPE sources. 2D III-nitrides semiconductors show great potential to provide more options in this field not only due to the chemical comparability to h -BN but also due to the mature development of their bulk phases, such as deep UV light-emitting diodes, , lasers diodes, , and transistors . Following theoretically confirming the good thermodynamic stability of hexagonal AlN ( h -AlN), Tsipas et al, Mansurov et al, and Malin et al had experimentally realized h -AlN via molecular beam epitaxy. The defective monolayer h -AlN is highly expected to be a good host material for qubits due to its similarity to h -BN.…”
Section: Introductionmentioning
confidence: 99%
“…Impurity doping turns out to be advantageous for regulating the coupling energy by introducing local lattice variation as well as additional Coulomb potential to QWs due to the Coulomb interaction between carriers and the charged dopant atoms. The Mg atom commonly serves as the acceptor for p-type doping in group-III nitrides, [29][30][31] and previous studies have reported that using Mg doping in InGaN MQWs can improve the hole injection and crystal quality, thus enhancing the performance of InGaN LEDs. 32,33 When Mg is doped in nitride via the substitution of Ga or Al, a local positive center is formed due to the lack of a single valence electron.…”
Section: Regulation Of Valence Quantum States Using Additional Potent...mentioning
confidence: 99%
“…The explosion of COVID‐19 has been greatly impacting the world and intensively activated the development of light‐emitting diodes (LEDs) at the ultraviolet‐C (wavelength ≤ 280 nm) emission range. It has been confirmed encouragingly perspective for the ultra‐fast sterilization toward SARS‐CoV‐2 within 1 s. [ 1–7 ] In the past decades, in order to fabricate high‐performance UVC‐LED, various techniques have been proposed to seek excellent crystalline AlN templates on UVC‐transparent sapphire substrates. [ 8–19 ] In spite that the epitaxial lateral overgrowth (ELOG) [ 4,20–22 ] and high‐temperature annealing (HTA) [ 23,24 ] strategies act as landmarks to fulfill the demands, both of them expose respective fatal shortcomings.…”
Section: Introductionmentioning
confidence: 99%